FAKTOR PERSONALITY ATAU LINGKUNGAN STUDI KOMPARASI TERHADAP NIAT PEMBELIAN ULANG PRODUK GREEN BEAUTY DI KABUPATEN ROKAN HULU - Maurisni, PUTRI; Rochmawati, Tiara; Savischa, Suriana (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2025)
This study aims to analyze and compare the influence of personality factors and environmental factors on repurchase intention of green beauty products in Rokan Hulu Regency. The research background is based on the growing public awareness of eco-friendly products, although challenges remain in encouraging repurchase, particularly in developing regions. A quantitative approach was employed with purposive sampling, involving consumers who had purchased and used green beauty products. Data were analyzed using Structural Equation Modeling (SEM) with validity, reliability, and hypothesis testing. The results indicate that both personality and environmental factors significantly affect repurchase intention. However, environmental factors (O = 0.386; T = 6.704; p = 0.000) exert a more dominant influence compared to personality factors (O = 0.244; T = 3.852; p = 0.000). This finding emphasizes that social norms, peer and family influence, as well as environmental awareness play a stronger role in determining repurchase decisions than individual characteristics. The R-square value of 0.302 suggests that the model explains 30.2% of the variance in repurchase intention, while the remaining variance is influenced by factors outside the model. The study concludes that green beauty marketing strategies in Rokan Hulu should focus more on strengthening social norms, community engagement, and environmental-based campaigns to enhance consumer loyalty. The practical implication is that companies should leverage the power of social environment, supported by personality-based segmentation, to sustain repurchase of eco-friendly products.